"comparison of perception of HIV/AIDS Risk and sexual Risk Behaviours Among Youths with and without Disabilities in Oyo State, Nigeria" (2015)
"The study investigated the perception of HIV/AIDS risk and sexual risk behaviours among youths with disabilities (WD) in comparison with youths without disabilities (cotnparison group)' The study adopted a cross-sectional survey with 362 participants comprising 181 WD with visual impaired 29(161o), physically challenged 40 (22.1Vo) and hearing impaired 112 (61'9Va) and comparison group (N = 181). A \9-item structured questionnaire was usedfor data collection' The instrument was revalidated and found to be highty reliable and valid for the study'Kruskal- Wallis test for dffirences was used to determine the dffirences in perception of HIV/AIDS risk and sexual risk behaviours among the two Sroups as well as t-test' The resufts showed that there was a significant dffirence in perception of HIV/AIDS risk between WD and the comparison Sroup tx, = (t) = 27.79, p < 0.01)l as well as a significant dffirence in sexual riskbehaviours amonS thetwoSroups[X,=(1)=23.117,p<0.01)].Thet-testalsorevealedasignificantdifference between the groups on sexual risk behaviours [t(360) = 4.926, p < 0.01)]and HIV/AIDS risk tt(360) = 5.301, P < 0.01)1. It was further reported that wD recorded higher sexual risk 'behaviour(i=9.35,5D=4'137,n=l8l)thanthecomparisongroup(=7'48'SD=3'008'n= 181). This trend was also reported on HIV/AIDS risk, with wD recording higher (= 14'56' SD = 6.537, n = 181) than the comparison group (= 11.23, SD = 5.385, n = j,81)' Thefindings ofthe paper were duly discussed withfar reaching recommendations for policy making' The study offers a new understanding of the perception of the HMAIDS risk and sexual risk behaviour in this group ofyouth population as well as provide relevant stakeholders with new vista in handling HIV/AIDS issues and sexualiry of the disabled'"